Tinjauan Kritis Penerapaan Presidential Threshold Pada Pemilihan Umum Serentak - Rikardo, Ofis (Direktorat Penelitian dan Pengabdian (DPPM) Universitas Pelita Bangsa, 2024)
The Presidential Threshold was applied in the election of president and vice president in Indonesia in the 2004 election. The implementation of the Presidential Threshold began during the 2004 Presidential Election based on Law Number 23 of 2003. Prior to the Constitutional Court decision Number 14/PUU-XI/2013, the implementation of the presidential election and Legislative elections are not held simultaneously. It was only later through this decision that the presidential election and legislative election were held simultaneously. Problems then arise when the Presidential Election still requires a Presidential Threshold when the presidential election and legislative election are held simultaneously (simultaneously).